2023
DOI: 10.1039/d2tb02377f
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional epoxy resin-based composites with excellent flexural strength and X-ray imaging capacity using micro/nano structured QF-Bi2SiO5 fillers

Abstract: Composites have been widely applied in various industries and are beneficial in attaining complicated functionalities. Particularly, for dental fiber posts or orthopedics implants, the composites should have excellent mechanical properties...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Therefore, to obtain sufficient strength, the fibers are usually modified using physical (sandblasting, corona treatment, and plasma spraying) and chemical methods (silane coupling agent treatment, sol-gel treatment, and polymer grafting) to improve their surface affinity and wettability and obtain good interfacial bonding with resin. [12][13][14][15][16][17] Bahramian et al introducing functional groups on the surface of the fibers by corona discharge to improve FRCs' mechanical properties due to formation of good interfacial bonding between the fibers and resin. However, it was found that high corona energy may leading to the deformation and/or rupture of the fibers, thereby decreasing fiber strength and affecting the strength of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain sufficient strength, the fibers are usually modified using physical (sandblasting, corona treatment, and plasma spraying) and chemical methods (silane coupling agent treatment, sol-gel treatment, and polymer grafting) to improve their surface affinity and wettability and obtain good interfacial bonding with resin. [12][13][14][15][16][17] Bahramian et al introducing functional groups on the surface of the fibers by corona discharge to improve FRCs' mechanical properties due to formation of good interfacial bonding between the fibers and resin. However, it was found that high corona energy may leading to the deformation and/or rupture of the fibers, thereby decreasing fiber strength and affecting the strength of the composite.…”
Section: Introductionmentioning
confidence: 99%